CAN PENAL MEDIATION SOLVE DOMESTIC VIOLENCE? INSIGHTS FROM ISLAMIC LAW - Kania, Dede; Rahmannillah , Vienka; Anggarainiko, Litya Surisdani (LITIGASI, 2024)
Domestic violence remains a pressing issue, with approximately 70% of cases resolved through penal mediation in recent years. In West Java Province alone, nearly 3,000 cases of domestic violence have been recorded, highlighting the urgency of effective resolution mechanisms. Penal mediation has emerged as an alternative approach, yet its alignment with Islamic legal principles remains underexplored. Islamic law strictly prohibits acts of violence, as it is a religion that upholds human dignity and peace. This study aims to examine the principles of Islamic law in the application of penal mediation to domestic violence cases and to identify the challenges faced in its implementation from both general and Islamic perspectives. Employing an empirical juridical method, this research gathers qualitative data through interviews, field observations, and literature reviews. The findings reveal a strong correlation between Islamic legal principles and penal mediation, with Surah An-Nisa verse 35 serving as a foundational reference for mediation efforts. However, the study also uncovers normative challenges, including inconsistencies in regulatory frameworks and misinterpretations of Islamic law regarding reconciliation and peace. The novelty of this research lies in its integration of Islamic legal principles with contemporary penal mediation practices, providing a unique perspective on addressing domestic violence. By bridging legal theory and religious doctrine, this study contributes to the development of more culturally and ethically grounded mediation practices, offering valuable insights for policymakers, legal practitioners, and religious scholars.